The Relationship Between Non-elite Sporting Activity and Calcaneal Bone Density in Adolescents and Young Adults: A Narrative Systematic Review - Patel, Hansa; Sammut, Luke; Denison, Hayley; Teesdale-Spittle, Paul; Dennison, Elaine (Frontiers in Physiology, 2020)
Introduction: Osteoporotic fracture represents a major public health burden. The risk of fragility fracture in late adulthood is strongly impacted by peak bone mass acquisition by the third decade. Weight bearing sporting activity may be beneficial to peak bone mass accrual, but previous studies have focused on elite sporting activity and used dual energy X-ray absorptiometry as a measure of bone density. The authors performed a narrative systematic review of individual recreational sports and calcaneal quantitative ultrasound (cQUS) bone measures in young people. Methods: Multiple databases were systematically searched, up until 31st March 2019. The authors included studies of participants aged 11 – 35 years reporting any level of habitual recreational sporting activity (HRSA) and cQUS measures, excluding elite/professional/competitive sporting physical activity. Studies (title and abstract) were screened independently by two reviewers and a third reviewer resolved any discrepancies. STROBE guidelines were used to check the reporting of observational studies. The Newcastle – Ottawa Scale was used to assess the risk of bias of the studies included in the review. The systematic review was registered with the International Prospective Register of Systematic Reviews (PROSPERO). Results: A search yielded 29,512 articles that considered relationships between bone density assessed by any technique and habitual recreational sporting activity. Duplicate and out of scope abstracts were removed. This left 424 papers which were screened by two reviewers, with six meeting inclusion criteria, including assessment by cQUS. The authors identified papers where sports considered included soccer (football), swimming, cycling, gymnastics, dancing, badminton, basketball, fencing, wrestling and judo. Although study heterogeneity prohibited meta-analysis, all six included studies reported significant benefits of weight bearing HRSA on cQUS outcomes. Conclusion: The potential long term effects of recreational sports with site specific changes as assessed by cQUS need further investigation, although the available literature suggests benefit.